Coronary CT Angiography as a Diagnostic and Prognostic Tool: Perspective from a Multicenter Randomized Controlled Trial: PROMISE - Bittner, Daniel O.; Ferencik, Maros; Douglas, Pamela S.; Hoffmann, Udo (Current Cardiology Reports, 2016)
The PROMISE (Prospective multicenter imaging study for evaluation of chest pain) trial compared the effectiveness of coronary CT angiography and functional testing as initial diagnostic test for patients with suspicion for stable coronary artery disease (CAD). With 10,003 patients randomized at 193 sites, the PROMISE trial provides a snapshot of real-world care for this very common presentation. Over a median follow-up of 25 months, PROMISE did not find significant differences in major clinical events (composite endpoint 164 vs. 151, HR 1.04 (0.83-1.29); p = 0.75) between the two strategies. Other major findings were the large discrepancy between estimates of pre-test likelihood and observed prevalence for obstructive CAD (≥50 %) and the proportion of noninvasive tests positive for ischemia or obstructive CAD (53 vs. 11 %; respectively) and the better efficiency of coronary computed tomography angiography (CTA) to select patients for invasive coronary angiography (ICA) who had obstructive CAD (72 vs. 48 % for coronary CTA and functional testing, respectively). Radiation exposure was higher in the CT arm compared to all functional testing but lower than for nuclear perfusion stress testing. Improvement of patient selection for diagnostic testing and risk stratification will be keys to increase efficacy and efficiency of management of patients with suspicion for stable CAD.
EVALuna2:33701